LAPORAN KASUS: HERPES ZOSTER PADA LANSIA - Dinda Mulya Arrifa; Hapsari Triandriyani; Hadi Firmansyah (Cahaya Ilmu Bangsa Institute, 2024)
ABSTRACT Background: Shingles is a viral infection of varicella zoster that affects the nerves and is characterised by a unilateral herpetic eruption on the skin. In general, shingles is a self-limiting disease, but in some cases it can cause complications. Objective: This case report aims to provide a diagnostic description and management of patients with Herpes zoster. Method: A case report of herpes zoster in an 83-year-old man. From anamnesis, complaints were found in the form of lesions on the neck, shoulders, right arm, and back that had appeared since four days before the patient was hospitalised. Dermatological and bacteriological examinations are performed to confirm the diagnosis. Results: This patient had clustered erythematous papules following a dermatome pattern on the neck, shoulder and right arm, and a risk factor of a history of chickenpox. This clinical picture is typical for herpes zoster, so other differential diagnoses can be ruled out. The patient was given Acyclovir 800 mg, taken five times a day for seven days, as the main antiviral drug. Conclusion: In general, shingles is a self-limiting disease, but in some cases it can cause complications. The prognosis of the disease is influenced by the age of the patient when infected. Patients under 50 years old have a better prognosis than patients over 50 years old. ABSTRAK Latar Belakang: Herpes zoster adalah infeksi virus varicella zoster yang memengaruhi saraf dan ditandai dengan erupsi herpes unilateral pada kulit. Pada umumnya, herpes zoster adalah penyakit yang dapat sembuh sendiri, tetapi pada beberapa kasus dapat menyebabkan komplikasi. Tujuan: Laporan kasus ini bertujuan untuk memberikan gambaran diagnostik dan penatalaksanaan pasien dengan Herpes zoster. Metode: Laporan kasus herpes zoster pada seorang pria berusia 83 tahun. Dari anamnesis ditemukan keluhan berupa lesi pada leher, bahu, lengan kanan, dan punggung yang muncul sejak empat hari sebelum pasien masuk rumah sakit. Pemeriksaan dermatologis dan bakteriologis dilakukan untuk memastikan diagnosis. Hasil: Pasien ini memiliki papula eritematosa bergerombol mengikuti pola dermatom di leher, bahu dan lengan kanan, dan faktor risiko riwayat cacar air. Gambaran klinis ini khas untuk herpes zoster, sehingga diagnosis banding lainnya dapat disingkirkan. Pasien diberikan Asiklovir 800 mg, diminum lima kali sehari selama tujuh hari, sebagai obat antivirus utama. Kesimpulan: Secara umum, herpes zoster adalah penyakit yang dapat sembuh sendiri, tetapi pada beberapa kasus dapat menyebabkan komplikasi. Prognosis penyakit ini dipengaruhi oleh usia pasien saat terinfeksi. Pasien berusia di bawah 50 tahun memiliki prognosis yang lebih baik daripada pasien berusia di atas 50 tahun.